Accelerated bioconversion of cow dung into concentrated organic fertilizer using microbial composition - Gulnaz F Rafikova; Tatyana Yu Korshunova; Elena V. Kuzina; Oleg N. Loginov (International Journal of Recycling of Organic Waste in Agriculture)
Purpose The purpose of this research was to evaluate the effectiveness of compositions based on the strains of microorganisms and intended for cow dung processing. Method Cow dung in an amount of 6 kg was placed into fermentation containers. To process the waste, we used microbial compositions. Sampling was performed on the 1st, 5th, 12th, 19th and 29th days. During the experiment, an analysis of microbiological, physicochemical and phytotoxic parameters was carried out. Results The number of micromycetes in the compostable mixture decreased by half compared to the control sample on the 5th day. When treated with microbial compositions at a dose of 25 ml/kg, no Salmonella bacteria was detected in the compostable mixture on the 29th day. In the variants of the experiment with the introduction of microbial compositions, the temperature increased to 45-51°C in a month after the experiment, the humidity decreased to 69%, and the pH of the compostable mixture was set at a neutral level. It was shown that the amount of total nitrogen increased by 7.1-38% when treated with microbial compositions. After 29 days in almost all experimental samples with the introduction of a liquid bacterial culture, the rate of germination and seedling emergence exceeded the growth rate of the control sample. Conclusion The possibility is shown to use the given compositions with bacteria of various functional groups as a basis of biological products for the accelerated processing of organic waste, such as cow dung.